Assessment of feigned cognitive impairment in severe traumatic brain injury patients with the Forced‐choice Graphics Memory Test. Issue 12 (13th October 2016) - Liu, Zilong; Dong, Juan; Zhao, Xiaohong; Chen, Xiaorui; Lippa, Sara M.; Caroselli, Jerome S.; Fang, Xiang
Abstract : The Forced‐choice Graphics Memory Test (FGMT) is a newly developed measure, based on binomial theorem, to assess feigned cognitive impairment. This study indicated that the FGMT can be used as a fast and reliable tool for identification of feigned cognitive impairment in patients with traumatic brain injury (TBI). Abstract: Introduction: The Forced‐choice Graphics Memory Test (FGMT) is a newly developed measure to assess feigned cognitive impairment. This study investigated the ability and reliability of FGMT for identification of malingering in patients with traumatic brain injury (TBI). Methods: The FGMT was administered to 40 healthy volunteers instructed to respond validly (Healthy Control, H‐C), 40 healthy volunteers instructed to feign cognitive impairment (Healthy Malingering, H‐M), 40 severe TBI patients who responded validly (TBI control, TBI‐C), and 30 severe TBI patients who evidenced invalid performance (TBI malingering, TBI‐M). Results: Both malingering groups (H‐M and TBI‐M) performed much more poorly than the nonmalingering groups (H‐C and TBI‐C). The FGMT overall total score, score on easy items, and score on hard items differed significantly across the four groups. The total score showed the highest classification accuracy in differentiating malingering from nonmalingering. A cutoff of less than 18 (total items) successfully identified 95% of TBI‐C and 93.3% of TBI‐M participants. The FGMT also demonstrated high test–retest reliability and internal consistency. FGMT scores were not affected by TBI patients' education, gender, age, or intelligence. Conclusion: Our results suggest that the FGMT can be used as a fast and reliable tool for identification of feigned cognitive impairment in patients with TBI.